Elaboration of Technological and Business Roadmap of the Circular Economy: a view on the energy sector - Tavares, Aline Souza (2021)
Circular Economy can be defined as a model, which seeks to extend the materials and product life extension in their greatest utility and value. In this context, this work objective present part of the doctoral thesis in development, since 2018, about Circular Economy Technological and Business Roadmap to elucidate technological and market trends for future investments and partnerships. The methodology for the Current Stage was carried out using specialized media and case studies in the Ellen MacArthur Foundation platform, and in the Long Term, with the analysis of scientific articles, relating them with the respective drivers. Among the results obtained, it is possible to highlight, in both temporal stages, the circular actions in Circular Design and Recycling, the Reverse Logistics and Product-service systems (PSS) business models, as well as the sectors most impacted: Petrochemical, Energy and Textile.